Superdiversity, social cohesion, and economic benefits - Paul Spoonley (IZA World of Labor, 2014)
Empirical studies have found that achieving superdiversity—a substantial increase in the scale and scope of minority ethnic and immigrant groups in a region—can provide certain economic benefits, such as higher levels of worker productivity and innovation. Other studies have found that these benefits can be compromised by political and populist anxieties about ethnic, religious, and linguistic diversity.
Keywords: J15; 330; ethnic diversity; social cohesion; innovation